(untitled) (Journal of Oriental Studies, 2024)
The teaching of the subject "History of Iranian Culture" has been included in the curriculum of the Chair of Iranian Studies of YSU in recent years. The inclusion of the course in the curriculum of the Chair of Iranian Studies is due to the students’ great interest in the topic and its relevance. It is the history of Iranian culture, from the cave-dwelling people and the first civilizations to the present day. The course provides a solid foundation for students to further understand Iranian literature and art, as well as political and diplomatic features. The teaching methodology of the subject was developed by the professor of the chair of Iranian studies and is based on existing, modern research. This article examines the teaching methodology developed by the lecturer, which has been used in YSU for five years. Keywords: History of Iranian Culture, teaching methodology, creative thinking, research, technology-enhanced collaborative learning